ABOUT SELF-EDUCATION AND ITS ROLE IN PERSONALITY DEVELOPMENT - Siddiqova Feruza Bakhtiyarovna (American Journals Publishing, 2023)
The article discusses independent education and its significance, aspects of the organization of independent education. Many aspects of independent learning and their positive impact on the level and quality of education are discussed.
Keywords: Extensive, orientation, compensatory, thinking, mind, reflection reaction, response reaction.